Wave propagation in sandwich structures with resonators and periodic cores. (May 2013) - Chen, JS; Sun, CT
Wave propagation in sandwich structures containing periodic cores and local resonators are studied. The effect on wave attenuation is emphasized. It is found that within certain frequency bands wave is forbidden from propagating through the structure with periodic cores or with resonators. It is also found that for the structure consisting of two different core materials periodically placed along the beam length, the location and range of the stop band can be tailored by the physical properties of the core. Also, with fixed core properties, the lattice constant becomes an important factor in controlling the location of the stop band. Moreover, the coupling of the two mechanisms can effectively enlarge the width of the stop band and enhance wave attenuation. It is evident that resonators are easier to use for filtering disturbances with low frequencies.